2012
DOI: 10.1016/j.molcel.2012.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic STAT3 Represses Autophagy by Inhibiting PKR Activity

Abstract: In a screen designed to identify novel inducers of autophagy, we discovered that STAT3 inhibitors potently stimulate the autophagic flux. Accordingly, genetic inhibition of STAT3 stimulated autophagy in vitro and in vivo, while overexpression of STAT3 variants, encompassing wild-type, nonphosphorylatable, and extranuclear STAT3, inhibited starvation-induced autophagy. The SH2 domain of STAT3 was found to interact with the catalytic domain of the eIF2α kinase 2 EIF2AK2, best known as protein kinase R (PKR). Pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
184
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 238 publications
(191 citation statements)
references
References 55 publications
6
184
0
1
Order By: Relevance
“…Wild-type STAT3 and nonphosphorylatable STAT3 Y705F transfected into U2OS cells inhibit baseline as well as starvation-induced EIF2A phosphorylation, further confirming this hypothesis. 14 The phosphorylation of EIF2A mediates general translational arrest and promotes the selective transactivation of stress response genes. Cells carrying a nonphosphorylatable EIF2A (S51A) mutant fail to induce autophagy in starvation conditions, suggesting that EIF2A phosphorylation of serine 51 plays a major role in autophagy regulation.…”
Section: Regulation Of Autophagy By Cytoplasmic Stat3mentioning
confidence: 99%
See 1 more Smart Citation
“…Wild-type STAT3 and nonphosphorylatable STAT3 Y705F transfected into U2OS cells inhibit baseline as well as starvation-induced EIF2A phosphorylation, further confirming this hypothesis. 14 The phosphorylation of EIF2A mediates general translational arrest and promotes the selective transactivation of stress response genes. Cells carrying a nonphosphorylatable EIF2A (S51A) mutant fail to induce autophagy in starvation conditions, suggesting that EIF2A phosphorylation of serine 51 plays a major role in autophagy regulation.…”
Section: Regulation Of Autophagy By Cytoplasmic Stat3mentioning
confidence: 99%
“…A wide range of RTKs phosphorylate STAT3 directly or via SRC kinase, and several studies have proven that blocking kinases such as KDR, PDGFRB, and ALK results in enhanced autophagy by subsequent inhibition of the STAT3 pathway (Table 3). 14,41,42,50,[74][75][76][77][78][79][80][81][82][83] Currently, several JAK-STAT inhibitors are being examined in clinical trials for cancer therapy. For example, in a phase II clinical trial to treat metastatic pancreatic cancer, ruxolitinib together with capecitabine showed a benefit for overall survival and progression-free survival compared with a placebo plus capecitabine used in second-line therapy, promoting the application of JAK-STAT inhibitors in cancer therapy.…”
Section: Implication Of Stat3-regulated Autophagy In Cancer Therapeuticsmentioning
confidence: 99%
“…17,[27][28][29] Antigen retrieval was performed by incubating slides in citrate buffer (pH 7.3) for 20 min at 98 C and cooling them for 30 min, at room temperature (RT). The sections were mounted on Shandon Sequenza coverplates (Thermo Fisher Scientific, 72-199-50) in distilled water.…”
Section: Phospho-eif2amentioning
confidence: 99%
“…16 Moreover, PA causes the disruption of inhibitory signal transducer and activator of transcription 3-RNA-dependent protein kinase interactions, which facilitates autophagy induction. 17 In contrast, a high-fat diet (HFD) downregulates autophagy by reducing autophagosome/lysosome fusion, 18 as well as by decreasing the number and the acidity of lysosomes. 19 The conflicting results may be attributed to differences in cell types, observation period, FFAs concentration and, more likely, difficulty in monitoring autophagic flux in vivo.…”
mentioning
confidence: 99%